Phenotyping Local Eggplant Varieties: Commitment to Biodiversity and Nutritional Quality Preservation - Martínez-Ispizua, Eva; Calatayud, Ángeles; Marsal, José Ignacio; Mateos-Fernández, Rubén; Díez, María José; Soler, Salvador; Valcárcel, José Vicente; Martínez-Cuenca, Mary-Rus (Frontiers in Plant Science, 2021)
Given the little variability among commercialised eggplants mainly in developed countries, exploring and structuring of traditional varieties germplasm collections have become a key element for extending ecotypes and promoting biodiversity preservation and consumption. Thirty-one eggplant landraces from Spain were characterised with 22 quantitative and 14 qualitative conventional morphological descriptors. Landraces were grouped based on their fruit skin colour (black-purple, striped, white and reddish). Landraces B7, B20 and B24 were left out for their distinctive fruit characteristics. Wide variation for plant, leaf, flower and fruit phenology traits was observed across the local landraces, and fruit descriptors were considered the most important ones. In a second experiment, landraces, B14, B16 and B17 were selected to determine fruit quality. By contemplating the benefits provided by antioxidants and sugars for human health, pulp antioxidant capacity, total phenolic, ascorbic acid, carotenoid, flavonoid and total sugar content were determined. Significant differences were observed across these three landraces, and B14 was highlighted for its antioxidant properties, while B17 stood out for its high sugar content. B16 did not stand out for any traits. The results indicate the wide variability in eggplants for their phenotypic and nutritional characteristics, which emphasises the importance of traditional varieties as the main source of agricultural biodiversity.